Working Time Allocation of Seaweed Colector Households in Kecamatan Cikelet; Garut West Java - Moch Prihatna Sobari; A Fachrudin; A Sujana (Buletin Ekonomi Perikanan, 1996)
Collecting seaweed was done not only by fisherman households but also by farmer household and plant labour households. This fenomena indicate that household allocated their family members for different kind of work increase household income. Household leader seems spend much time than members which indicate the role of leader in every household. Rate of participation decrease from adult to teenager and from man to women. Farmer household has higher duration time than fisheries household. Duration time of all households still quite low.